In vitro and In vivo Screening of Medicinal Plants for their Anti-Inflammatory Activity - Raj, Shubham; Mandal, Snigdha Das (Journal of Pharmacy Practice and Community Medicine)
Inflammation is a natural defense mechanism of the body in response to harmful stimuli such as pathogens, injuries, or irritants. However, chronic inflammation is associated with many disease including arthritis, asthma, and cardiovascular disorders. Although synthetic anti-inflammatory drugs are widely used, they often have adverse effects and limitations. Therefore, medicinal plants have gained attention due to their traditional use and natural therapeutic potential. This review focuses on both in vitro and in vivo screening methods used to evaluated the anti-inflammatory activity of various medicinal plants. In vitro methods such as membrane stabilization, protein denaturation and nitric-oxide inhibition provide rapid and cost-effective preliminary results. In vivo models, including carrageenan induced paw edema and formalin induced paw edema offer a more comprehensive evaluation in living systems. This article summarize the finding of several studies that have 0the development of safer and effective anti-inflammatory agents (Phanse, 2012).
Keywords: Anti-inflammatory activity; Herbal Medicine; In vitro model; In vivo model; Medicinal Plants